Effect of carbohydrate counting using bolus calculators on glycemic control in type 1 diabetes patients during continuous subcutaneous insulin infusion. Issue 4 (19th January 2017) - Yamada, Eijiro; Okada, Shuichi; Nakajima, Yasuyo; Bastie, Claire C; Tagaya, Yuko; Osaki, Aya; Shimoda, Yoko; Shibusawa, Ryo; Saito, Tsugumichi; Ozawa, Atsushi; Yamada, Masanobu
Abstract: The present study examined the long‐term efficacy of insulin pump therapy for type 1 diabetes patients when carried out using carbohydrate counting with bolus calculators for 1 year. A total of 22 type 1 diabetes patients who had just started continuous subcutaneous insulin infusion were examined and divided into two groups: one that was educated about carbohydrate counting using bolus calculators ( n = 14); and another that did not use bolus calculators ( n = 8). After 1 year, the hemoglobin A1c levels of the patient group that used bolus calculators decreased persistently and significantly ( P = 0.0297), whereas those of the other group did not. The bodyweight, total daily dose of insulin and bolus percentage of both groups did not change. Carbohydrate counting using bolus calculators is necessary to achieve optimal and persistent glycemic control in patients undergoing continuous subcutaneous insulin infusion. Abstract : This study aimed to examine the long‐term efficacy of insulin pump therapy for type 1 diabetes patients when performed using carbohydrate counting using bolus calculators for 1 year. After 1 year, the hemoglobin A1c levels of the patient group that used bolus calculators decreased persistently and significantly ( P = 0.0297) while that of the other group did not. Carbohydrate counting using bolus calculators is necessary to achieve optimal and persistent glycemic control in patients undergoing continuous subcutaneous insulin infusion.